The Efforts of the Pastor as a Christian Educator in Preventing Interreligious Marriages for Young Christian Youth - Siliwarti; Henni Somantik; Markus Amid; Marthen Mau (PT FORMOSA CENDEKIA GLOBAL, 2024)
Humans live in various tribes, nations, cultures, customs and religions, because diversity cannot be denied so that marriages of different beliefs can occur in society. The occurrence of inter-faith marriages is caused by a lack of awareness among young people regarding the impacts that occur when entering into inter-faith marriages. Based on the current prevalence of interfaith marriages, it is necessary for pastors as Christian educators to make efforts to prevent interfaith marriages from continuing to occur. Through this research, the aim is to explain precisely the efforts of pastors as Christian educators in preventing interfaith marriages for young people in GKII Jerusalem Sebelantau, Sekadau Regency. Researchers used descriptive qualitative research methods through observation, interviews and literature techniques. The results of the research obtained are that if the pastor as a Christian educator continuously educates, teaches, guides, and directs Christian young people to the right path through the word of God, then young people will not enter into interfaith marriages even if there is an interfaith marriage. religion, then through God's help can win for the glory of Christ